The Interaction between HLA‐DRB1 and Smoking in Parkinson's Disease Revisited. Issue 9 (10th July 2022) - Domenighetti, Cloé; Douillard, Venceslas; Sugier, Pierre‐Emmanuel; Sreelatha, Ashwin Ashok Kumar; Schulte, Claudia; Grover, Sandeep; May, Patrick; Bobbili, Dheeraj R.; Radivojkov‐Blagojevic, Milena; Lichtner, Peter; Singleton, Andrew B.; Hernandez, Dena G.; et al.
Abstract: Background: Two studies that examined the interaction between HLA‐DRB1 and smoking in Parkinson's disease (PD) yielded findings in opposite directions. Objective: To perform a large‐scale independent replication of the HLA‐DRB1  × smoking interaction. Methods: We genotyped 182 single nucleotide polymorphism (SNPs) associated with smoking initiation in 12 424 cases and 9480 controls to perform a Mendelian randomization (MR) analysis in strata defined by HLA‐DRB1 . Results: At the amino acid level, a valine at position 11 (V11) in HLA‐DRB1 displayed the strongest association with PD. MR showed an inverse association between genetically predicted smoking initiation and PD only in absence of V11 (odds ratio,  0.74, 95% confidence interval,  0.59–0.93, PInteraction  = 0.028). In silico predictions of the influence of V11 and smoking‐induced modifications of α‐synuclein on binding affinity showed findings consistent with this interaction pattern. Conclusions: Despite being one of the most robust findings in PD research, the mechanisms underlying the inverse association between smoking and PD remain unknown. Our findings may help better understand this association. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society